Pyrrolizidine alkaloids. - Robertson, J; Stevens, K (Royal Society of Chemistry, 2014)
This review covers pyrrolizidine alkaloids isolated from natural sources. Topics include: aspects of structure, isolation, and biological/pharmacological studies; total syntheses of necic acids, necine bases and closely-related non-natural analogues.